Pengaruh Iklim Organisasi terhadap Kinerja Pt. Industri Telekomunikasi Indonesia (Inti) Persero Bandung - Boby Novika (Journal of Education on Social Science (JESS), 2018)
The purpose of this study was to determine whether there was a positive and significant influence of organizational climate on performance in PT INTI Bandung. This study used a quantitative method. Data were collected through literature study and field study with observation, interview, and questionnaire towards 42 respondents. The number of samples in this study was obtained through simple random sampling technique. Research instruments were grouped into two variables, that is variable X (Climate Organization) and variable Y (Employee Performance). Data obtained from questionnaires were tabulated based on frequent frequencies, presented and analyzed qualitatively. Meanwhile, to find the influence between the two variables of this study the researchers used simple linear regression analysis techniques. Based on the results of the research it could be concluded that there was a positive and significant influence of organizational climate on companies performance of PT. INTI Bandung shown by simple linear regression equation Y = 5,53 + 0,688X. That is, the regression coefficient of 0.688 stated that each addition (due to the + sign) one score of the organization's climate value would give a score increase of 5.53 to the companies performance.